Liquidity Risk and Mutual Fund Performance - Dong, Xi; Feng, Shu; Sadka, Ronnie (Management Science, 2019)
This paper demonstrates that the ability of fund managers to create value depends on market liquidity conditions, which in turn introduces a liquidity risk exposure (beta) for skilled managers. We document an annual liquidity beta performance spread of 4% in the cross section of mutual funds over the period 1983–2014. Liquidity risk premia explain an insubstantial fraction of this spread; instead, the spread can be attributed to the differential ability of high liquidity beta funds to outperform across high and low market liquidity states, due to a differential rate of either mispricing correction or intensity of informed trading. Tests based on mispricing, proxied by a comprehensive set of 68 anomalies, and tick-by-tick trades, from a large proprietary institutional trading data set, corroborate the contribution of these channels. The results highlight the interaction between informed investors, mispricing, and liquidity beta. The Internet appendix is available at https://doi.org/10.1287/mnsc.2017.2851 . This paper was accepted by Neng Wang, finance.